النظم السياسية والإدارية في مملكة غرناطة في عصر بني الأحمر - مباركة , ابراهيم , بوغنامة بورقعة (جامعة الوادي University of eloued, 2018)
جاءت الدراسة بعنوان النظم السياسية والإدارية في مملكة غرناطة عهد بني الأحمر(635 ـــــ 897 هـــ/1238ـــــ 1492م),فالنظم هي جمع نظام والنظام بدوره يحوي عدة معاني,أبرزها التأليف والطريق والعادة,أما النظام في الشرع فهو الأحكام والقواعد التي وضعها الشارع لتنظيم وضبط أعمال متنوعة,والنظام السياسي والإداري هو الآخر عنصر مهم لا يمكن الاستغناء عنه,إذ من خلاله يتم تحديد علاقة السلطة بالرعية,ولقد عالجت دراستنا هذه التساؤل الرئيسي المتمثل في :كيف كانت النظم السياسية والإدارية في مملكة غرناطة أثناء فترة بني الأحمر؟,كما اندرجت تحت هذا التساؤل الرئيسي أسئلة فرعية أهمها ماهي أبرز الخطط السياسية للملكة ؟وما هي أهم المناصب الإدارية التي عرفتها غرناطة؟ هذا وقد اعتمدنا في دراستنا هذه بعض المناهج أبرزها المنهج التاريخي وبعض المناهج الأخرى المساعدة كالتحليلي والوصفي,كل هذا من أجل توضيح معالم النظم السياسية والإدارية لغرناطة عهد بني الأحمر. كما توصلنا في نهاية دراستنا لبعض النتائج ولعل أبرزها : لقد كان السلطان في مملكة غرناطة هو الرجل الأول في الدولة,وذلك كونه ممثلا للسلطة العليا في البلاد, - كان قصرالحمراء هو قاعدة ملوك بني نصر. - عرفت هذه المملكة خطة الحجابة, بصفته واسطة بين السلطة والرعية. - تعتبرالوزارة من أهم المناصب السياسية في مملكة غرناطة وكانت وزارة تنفيذية - عرفت دولة بني الأحمر خطط إدارية لها علاقة بالدين كالقضاء وأخرى لها علاقة بالجانب الاقتصادي كالحسبة,وأخرى لها علاقة بالجانب الأمني كالشرطة. The system is a collection system and the system in turn contains several meanings, most notably the composition and the road and the usual, but the system in the Sharia is the provisions and rules set by the street to organize and control the various works, The political and administrative system is the other indispensable element, through which the relationship of power to the parish is determined. Our study addressed this main question: How were the political and administrative systems in the Kingdom of Granada during the period of the Red? , And included under this main question sub-questions, the most important of which are the most prominent political plans of the Queen? What are the most important administrative positions that Granada knew? In this study, we have adopted a number of approaches, most notably the historical approach and some other analytical and descriptive methods, all in order to elucidate the political and administrative systems of Granada in the era of the Bani al-Ahmar. As we reached at the end of our study some of the most prominent results: The Sultan of the Kingdom of Granada was the first man in the state, as the representative of the supreme authority of the country, The Red Palace was the base of the kings of Bani Nasr. This kingdom defined the plan of the jubilee, as a mode between the authority and the parish. The ministry is considered one of the most important political posts in the Kingdom of Granada and it was an executive ministry. The State of Bani Al-Ahmar has defined administrative plans related to religion such as the judiciary and others related to the economic aspect such as the law, and others related to the security aspect such as the police.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي الوسيط و الحديث
Keywords: النظم السياسية والإدارية، غرناطة، بني الأحمر; Systèmes politiques et administratifs, Grenade, Bani al-Ahmar; Political and administrative systems, Granada, Bani al-Ahmar